Drie eeuwen Banya : de geschiedenis van een Surinaamse slavendans - Martinus-Guda, Trudi (Ministerie van Onderwijs. Afdeling Cultuurstudies ParamariboSR, 2005)
Presents a descriptive study of a dance called Banya, which achieved its greatest popularity in the 19th century, where this slave entertainment was also used by the colonial elite as a tool in its political squabbles.